A novel method for contributing to composting start-up at low temperature by inoculating cold-adapted microbial consortium. (August 2017) - Xie, Xin-Yu; Zhao, Yue; Sun, Qing-Hong; Wang, Xue-Qin; Cui, Hong-Yang; Zhang, Xu; Li, Yan-Jie; Wei, Zi-Min
Graphical abstract: Highlights: CAMC has high activity of degradation biomass waste at low temperature. CAMC can change the bacterial community composition and succession of composting. Inoculated CAMC contribute to start-up in winter composting. The energy produced by CAMC would be a clean heat supply source for heating-up. Abstract: Low temperature climate presented a technical challenge to start-up composting in northern region of China. This study investigated if the cold-adapted microbial consortium (CAMC) could promote composting start-up at low temperature. In this work, the CAMC was inoculated when food waste was composted at 10 °C. The results showed that inoculating CAMC accelerated the piles temperature effectively, the piles passed through the start-up period within 37 h. Moreover, the inoculants could enhance the abundances of dominant strains related to organic matters degradation rate. Redundancy analysis (RDA) indicated that the relationships among indigenous bacteria, organic substrates degradation and temperature evolution were influenced by the inoculants. Furthermore, the heat generation value and degradation rate of the hydrolysable carbohydrate, lipids and protein were significantly enhanced with CAMC inoculated. This work demonstrated that inoculating CAMC was beneficial to composting self-heating, it provided a novel biotechnology support to ensure the normal start-up of winter composting.